The Role of Psychological Pricing and Perceived Value in Driving Purchase Decisions: Managerial and Digital Entrepreneurship Perspectives - Utami, Budi; Hidayat, Syamsul; Setyariningsih, Eny (CV. Ulil Albab Corp, 2025)
This study aims to analyze the role of psychological pricing strategies and perceived value in influencing consumer purchasing decisions, with an emphasis on managerial and digital entrepreneurship perspectives. The main focus of this research is Generation Z consumers in East Java who actively make transactions on TikTok Shop, as one of the rapidly growing social commerce platforms. A quantitative approach was used with a probability sampling method on 227 respondents. The results of the study show that low price strategies and flash sales, which are designed based on a psychological approach, significantly influence consumer value perceptions and have a direct impact on purchasing decisions. Perceived value acts as an important mediator that strengthens the influence of both strategies on purchase intentions. In the context of digital entrepreneurship, these findings are relevant because they show how business actors can utilize pricing mechanisms based on consumer psychology to increase sales conversions, loyalty, and shopping experiences. The practical implications of this study indicate that digital MSMEs must integrate pricing strategies with an understanding of digital consumer behavior in order to be able to compete in a competitive and dynamic social platform-based e-commerce ecosystem.